Mean-Field and Monte Carlo Studies of the Magnetic Properties of a Spin-7/2 and Spin-5/2 Ising Bilayer Film - YESSOUFOU, RACHIDI ADENIYI AKAMBI (My University, 2018)
We use standard Monte Carlo simulations based on the Metropolis algorithm and mean-field calculations to investigate the magnetic properties of an Ising bilayer film consisting of two superposed ferromagnetic squared lattices A and B whose magnetic atoms have spin 7/2 and 5/2 respectively. Crystal-field and external magnetic field effects on the spins are considered in the model. The magnetic order parameters and response functions are calculated as functions of the temperature for selected values of the model parameters and this enables one to devise thermal phase diagrams by both methods. Our calculations only reveal second-order phase boundaries. Under appropriate conditions, compensation point phenomena are detected in the calculations below the critical temperatures. When the system is exposed to the external magnetic constraint, attracting hysteresis phenomena are sometimes generated. The temperature dependence of the coercitive field for various values of the crystal-field is singled out.
Keywords: Monte Carlo simulations · Mean-field calculations · Ising bilayer film · Compensation temperature ·; Temperature phase diagram · Hysteresis phenomena